Public Libraries Engaging Communities through Technology and Innovation: Insights from the Library Living Lab. Issue 1 (2nd January 2022) - Hernández-Pérez, Oskar; Vilariño, Fernando; Domènech, Miquel
ABSTRACT: Public libraries have proven for centuries to be infrastructures both stable enough as reference centers for access to knowledge yet plastic enough to respond to the social changes of the communities they serve. In these present times of transformation, during which digitalization and the intensive use of technologies are modifying the way in which knowledge is produced, public libraries are facing new and disruptive challenges. The emergence of certain innovation ecosystems within libraries, which place the community at the center of cocreation and codesign processes between different agents, has transformed some public libraries into encountering spaces. The Library Living Lab, in the Miquel Batllori Public Library of Sant Cugat del Vallès (Barcelona, Spain), is an expression of this systemic change. The following paper is a case study based on that sociotechnical infrastructure and analyzes, through two singular examples, how digital technologies can be drivers of social transformation when citizen engagement is placed at the center of innovation processes. The case study also provides insights into how public libraries may become key agents in fostering and strengthening social cohesion through situated, collective, and technology-based innovation practices.